KELAYAKAN BOOKLET MATERI KEANEKARAGAMAN HAYATI BERDASARKAN MORFOLOGI DAN KANDUNGAN GIZI BUAH TEPO, KEREKE, PIRIT - Holilah, Siti; Daningsih, Entin; Titin, Titin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed to determine the feasibility of booklet as the media based on morphology  for tepo, kereke and pirit  and nutrient fruit tepo, kereke and pirit on the materials of different levels of biodiversity of tenth grade of Senior High School. This research is a descriptive study.  Data collection were done y using the validation instrument. The validation were done by 5 validators.  2 validators are the lecturers of biology education, while 3 others are the high school biology teachers using curriculum 2013 for tenth grade . The results of the validation booklet with 6 aspects ie consistency, format, organization, attraction, font size, space is empty and 13 criteria  got CVR value =   0.99 according to the minimum value of the CVR Lawshe to 5 validators is 0.99 so media  booklet were categorized as valid and declared as viable media for learning on the various levels of biodiversity material of tenth grade of Senior High School. Keywords: Booklet, Fruit tepo, kereke, pirit, Morphology, Nutritional content